Increasing Trend of Swimming and Water Sports in Pakistan Causing Ear Related Problems - Iqbal Hussain Udaipurwala (Journal of Bahria University Medical and Dental College)
Swimming and other water sports are the important human activities to keep them physically fit and vigorous. Pakistan has a population of over 183 million1 and millions of people are involved in swimming and other water sports activities in Pakistan. This trends is increasing tremendously in the recent past. There are many reasons for this increasing trend but following are the top most factors: · Increasing urbanization. · Increasing obesity and thus more people are involved in such activities. · Increasing facilities for swimming and water sports.